2009
DOI: 10.1007/s00239-009-9263-0
|View full text |Cite
|
Sign up to set email alerts
|

Acyl-CoA Dehydrogenases: Dynamic History of Protein Family Evolution

Abstract: The acyl-CoA dehydrogenases (ACADs) are enzymes that catalyze the α,β-dehydrogenation of acyl-CoA esters in fatty acid and amino acid catabolism. Eleven ACADs are now recognized in the sequenced human genome, and several homologs have been reported from bacteria, fungi, plants, and nematodes. We performed a systematic comparative genomic study, integrating homology searches with methods of phylogenetic reconstruction, to investigate the evolutionary history of this family. Sequence analyses indicate origin of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
88
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(91 citation statements)
references
References 53 publications
(54 reference statements)
3
88
0
Order By: Relevance
“…Similar to S. Gallinarum, S. Enteritidis SPI-14 contains six open reading frames (ORFs) (SEN0800 to SEN0805). We identified one SPI-14 mutant with an insertion in SEN0803, which encodes a putative acyl-coenzyme A (Co-A) dehydrogenase that participates in alpha and beta dehydrogenation of acyl-CoA esters in both fatty acid and amino acid metabolism (92). In S. Typhimurium, a fatty acyl-CoA dehydrogenase is important for survival under conditions of carbon starvation (86), whereas in the plant pathogen Burkholderia cenocepacia, this enzyme is required for rough-colony morphology, biofilm production, and virulence (89).…”
Section: Resultsmentioning
confidence: 99%
“…Similar to S. Gallinarum, S. Enteritidis SPI-14 contains six open reading frames (ORFs) (SEN0800 to SEN0805). We identified one SPI-14 mutant with an insertion in SEN0803, which encodes a putative acyl-coenzyme A (Co-A) dehydrogenase that participates in alpha and beta dehydrogenation of acyl-CoA esters in both fatty acid and amino acid metabolism (92). In S. Typhimurium, a fatty acyl-CoA dehydrogenase is important for survival under conditions of carbon starvation (86), whereas in the plant pathogen Burkholderia cenocepacia, this enzyme is required for rough-colony morphology, biofilm production, and virulence (89).…”
Section: Resultsmentioning
confidence: 99%
“…Acyl-CoA dehydrogenases are enzymes that participate in alpha and beta dehydrogenation of acyl-CoA esters in both fatty acid and amino acid metabolism (53). Examination of the closely related B. cenocepacia J2315 genome sequence revealed that there are several paralogs of acyl-CoA dehydrogenases, and these enzymes may act on structurally different fatty acids or fatty acids of different lengths (27,30).…”
Section: Discussionmentioning
confidence: 99%
“…However, the surprising (universal?) presence of the ACAD-11 protein of unknown function in peroxisomes [19][20][21] might indicate a different scenario. The protein is of alpha-bacterial origin and most likely came along with the pre-mitochondrial bacterium.…”
Section: Reconstructing Steps Leading To Peroxisomesmentioning
confidence: 99%